The Brilliance of the Zebrafish Model: Perception on Behavior and Alzheimer’s Disease - Shenoy, Avinash; Banerjee, Meheli; Upadhya, Archana; Bagwe-Parab, Siddhi; Kaur, Ginpreet (Frontiers in Behavioral Neuroscience, 2022)
Alzheimer’s disease (AD) has become extremely prevalent in the elderly and aging population across the world. It’s pathophysiological markers such as overproduction along with the accumulation of Aβ senile plaques and neurofibrillary tangles (NFT) are posing a grave challenge to novel drug development processes. A model which simulates the human neurodegenerative mechanism will be beneficial for rapid screening of new therapeutic drugs. Zebrafish, as a successful model for Alzheimer’s disease (AD), is emerging rapidly due to the resemblance of neurological networks between the zebrafish and humans. This model has been thoroughly validated through research in aspects of neuronal pathways analogous to the human brain. The behavioural development patterns in zebrafish are also well established. The cholinergic, glutamatergic and GABAergic pathways, which play a role in the manifested behaviour of the zebrafish, are well defined. There are several behavioral models in both adult zebrafish and larvae to establish various aspects of cognitive impairment including spatial memory, associative memory, anxiety and other such features that are manifested in AD. Furthermore, zebrafish model eliminates the shortcomings of previously recognised mammalian models, in terms of expense, extensive assessment durations, and the complexity of imaging the brain to test the efficacy of therapeutic interventions. This review highlights the various models that analyse the changes in the normal behavioural patterns of the zebrafish when exposed to AD inducing agents. The mechanistic pathway adopted by drugs and novel therapeutic strategies can be explored via these behavioral models and their efficacy to slow the progression of AD can be evaluated.